Chapter 7 WIDESPREAD ZOANTHUS AND PALYTHOA DOMINANCE, BARRENS, AND PHASE SHIFTS IN SHALLOW WATER SUBTROPICAL AND TROPICAL MARINE ECOSYSTEMS - JAMES DAVIS REIMER; HIN BOO WEE; CATAIXA LÓPEZ; MARIA BEGER; IGOR CRISTINO SILVA CRUZ (Taylor & Francis, 2021)
oceanography, climate change, reefs, marine science, marine conservation, marine research
English[eng]
Keywords: bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; oceanography, climate change, reefs, marine science, marine conservation, marine research